Analysis Of The Role Of Regional Governments And The Ministry Of Law And Human Rights In The Formation And Harmonization Of Draft Regional Regulations After UU Nomor 15 Tahun 2019 - Mu'ammar, Thoyyib; Diamantina, Amalia (Dinasti Research, 2025)
Law Number 12 of 2011 concerning the Establishment of Legislations, was established with the hope that it can serve as a guide in the formation of laws and regulations which are implemented in a definite, standard, and standard manner and method that binds all institutions authorized to form laws and regulations. . However, during its implementation there were several problems in its implementation. Based on this, Law No. 15 of 2019 concerning Amendments to Law No. 12 of 2011 was promulgated on the Establishment of Legislation. One of the changes in Law No. 15 of 2019 is the authority to harmonize, unify, and consolidate the conception of the Draft Regional Regulation which was originally the authority of the Regional Government to become the authority of the Ministry of Law and Human Rights as long as the Ministry or Institution that carries out affairs in the field of Formation of Legislative Regulations Invitation has not yet been formed. The impact of the change in authority is the occurrence of a wave of requests for harmonization to the Regional Office of the Ministry of Law and Human Rights in Central Java. This thesis research aims to determine the role of the Regional Office of the Ministry of Law and Human Rights of Central Java in the process of harmonizing, concluding, and strengthening the conception of the Draft Regional Regulation, legal consequences, obstacles faced, and solutions. The type of this thesis research is descriptive qualitative and sociological juridical approach method. By using the theory of the rule of law, the theory of statutory science, and the theory of the formation of laws and regulations from the perspective of Islamic law as the basis for the study, it was concluded that the role of the Regional Office of the Ministry of Law and Human Rights of Central Java was as an extension of the Ministry of Law and Human Rights of the Republic of Indonesia in harmonizing the Draft Law. Regional Regulations in accordance with the provisions of laws and regulations both vertically and horizontally, Pancasila, the 1945 Constitution of the Republic of Indonesia and ensure that the formation of Provincial/Regency/City Regional Regulations is in accordance with the provisions of the establishment of laws and regulations. The obstacle faced is the lack of coordination which causes it to seem to extend the mechanism for the formation of laws and regulations in the regions.